2016
DOI: 10.1111/sum.12278
|View full text |Cite
|
Sign up to set email alerts
|

Farmer knowledge, perception and management of soils in the Las Vegas agricultural district, Madrid, Spain

Abstract: A sample group of 119 farmers from a semi‐arid district of Madrid was interviewed to determine the knowledge of individuals about soil conservation and management. Farmers commonly identify physical factors in the landscape that are visually recognizable and those chemical factors that clearly affect productivity. Often, factors, such as salinity or pH that require laboratory analysis, are less readily identified. Farmer knowledge of soils is influenced by their main source of income, gender, education and age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Lack of awareness, knowledge and skills have been widely cited as barriers to farmer uptake of practices, such as minimum tillage, cover crops and residue management (Ingram et al., 2014; Pronk, 2015; Renske, 2017). A survey of 119 farmers in a semi‐arid district of Madrid, Spain found that farmers were aware of their own knowledge limitations with respect to soil improvement and conservation and suggested awareness raising, capacity building, technical and policy support to address this (Barbero‐Sierra et al., 2016). However, in other contexts, farmers are well informed and supported, in Denmark, for example, (Table ), and in Scotland, where a small number of farmers interviewed reported accessing and interpreting sufficient field scale soil data (nutrient and structure) through a range of soil testing and interpretation techniques, including sampling and laboratory‐based analysis, GPS soil mapping and soil structure scanning, provided by commercial companies (Prager & McKee, 2014).…”
Section: Current and Emerging Practitioner Knowledge Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of awareness, knowledge and skills have been widely cited as barriers to farmer uptake of practices, such as minimum tillage, cover crops and residue management (Ingram et al., 2014; Pronk, 2015; Renske, 2017). A survey of 119 farmers in a semi‐arid district of Madrid, Spain found that farmers were aware of their own knowledge limitations with respect to soil improvement and conservation and suggested awareness raising, capacity building, technical and policy support to address this (Barbero‐Sierra et al., 2016). However, in other contexts, farmers are well informed and supported, in Denmark, for example, (Table ), and in Scotland, where a small number of farmers interviewed reported accessing and interpreting sufficient field scale soil data (nutrient and structure) through a range of soil testing and interpretation techniques, including sampling and laboratory‐based analysis, GPS soil mapping and soil structure scanning, provided by commercial companies (Prager & McKee, 2014).…”
Section: Current and Emerging Practitioner Knowledge Needsmentioning
confidence: 99%
“…Specifically for soil, the increasing complexities of managing multiple soil functions and a range of specialized, “smarter” yet sustainable systems, all call for qualitatively different sorts of advice which, not only provide technical support, but also build farmer capacity for SSM (Briggs & Eclair‐Heath, 2017). The knowledge needs of practitioners (farming, advisory and supply chain actors) and researchers in relation to soil and its resilience to agricultural and environmental change have been widely expressed, as have the demands for more guidance in implementing soil management practices and interpreting soil analysis (e.g., Barbero‐Sierra, Marques, Ruíz‐Pérez, Bienes, & Cruz‐Maceín, 2016; Dicks et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The additional learning opportunity of the workshops is that participants with little or no experience of soil testing or local knowledge on soil could interact with neighbouring farmers or extension staff who did. The workshop provides ample scope for peer‐to‐peer learning, which has been shown to be more effective than other extension techniques (Murage et al., ), as well as situate participants with people they rely on for new or specific knowledge (Barbero‐Sierra, Marques, Ruíz‐Pérez, Bienes, & Cruz‐Maceín, ), or are more likely to trust what they communicate in the workshop (Mase, Babin, Prokopy, & Genskow, ; Prokopy et al., ). However, it was also apparent that, without undertaking an entry survey of who was at the workshop, these learning opportunities would not be known to or could not be acted on by the extension providers.…”
Section: Resultsmentioning
confidence: 99%
“…Such a difference in water available for plants from 21.6 to 50.4 L per square meter can be used as an effective message to move land users to change into management practices aimed at increasing SOC content in agricultural soils. In this semiarid region, farmers perceive water as a priority [86], but not so the erosion processes [87] responsible for this situation. This is because farmers associate erosion only with extreme events and tend to ignore the long-term effects of unnoticed small losses [88].…”
Section: Discussionmentioning
confidence: 99%